Vitamin D supplementation: much ado about nothing. (3rd March 2020) - Gatti, D.; Bertoldo, F.; Adami, G.; Viapiana, O.; Lello, S.; Rossini, M.; Fassio, A.
Abstract: The scientific interest and the number of papers dealing with vitamin D supplementation has greatly grown in the last decades. Unfortunately, expert consensus on many clinical aspects of this topic is still lacking. In addition, data coming from recent clinical trials and meta-analyses seem to strongly put into doubt the real benefit of vitamin D supplementation, on both skeletal and extra-skeletal outcomes. This is further confusing since they seem to completely contradict the considerable body of evidence provided from previous epidemiological studies. This paper aims to analyze these new data in order to shed light onto the debated issues.